Regular build‐up of the spring phytoplankton maximum before ice‐break in a boreal lake. (23rd October 2015) - Salmi, Pauliina; Salonen, Kalevi
Abstract: The development of phytoplankton biomass and composition in a eutrophic boreal lake was studied during the evolution of under‐ice convection in spring. The results from 8 yr showed that, within a few weeks before ice‐break, phytoplankton biomass regularly increased by up to two or three orders of magnitude, reaching or exceeding the biomass in summer. Accordingly, this may be the most significant single annual phytoplankton episode in the lake. The development of phytoplankton was closely coupled with that of convection created by solar radiation at water temperatures < 4°C. In addition to vertical convection which keeps phytoplankton suspended, there was also horizontal convection which transported water with likely higher abundance of phytoplankton from the shallow lake margins. The effect of mechanical mixing, which was meant to prevent anoxia in the deep water layers of the study basin, was overridden by natural convection. Stochastic variations in weather played a key role controlling light penetration into the lake and hence the abundance and composition of under‐ice phytoplankton. After snow melt the proportion of motile algae was at first higher, sometimes with a maximum nearest to the ice, but later diatoms flourished throughout the convection layer. Only in the years of the shortest convection period did the proportion of motile algae remain high until the end of ice cover. More detailed information about the interaction between littoral and pelagial water masses under different mixing regimes is needed for a more profound understanding of the development of phytoplankton under‐ice.